PENGARUH PEMBERIAN FILTRAT BAWANG MERAH DENGAN BERBAGAI KONSENTRASI DAN ROOTONE-F TERHADAP PERTUMBUHAN STEK BATANG TANAMAN JAMBU BIJI (PSIDIUM GUAJAVA L) - MAYASARI, EVA (Universitas Negeri Surabaya, 2012)
Psidium guajava L. has a grade potensial in domestic market. The aim of research was to find out the different of concentrations of shallots extract and Rootone-F on vegetative growth of Psidium guajava L. by stem cutting. Complete Randome Design was used as the research methode in with 4 different concentrstions and 6 replicates. The result revealed that the concentrations of shallot extract affected on the vegetative growth. Beside that the result showed that concentrations was 18%-20% showed the best result for all growth parameters observed i.e. number of shoots, number of leaves, leaves wide, and number of roots.